Pengungkapan Perubahan Iklim Industri Pertambangan: Adakah Peran Struktur Kepemilikan? - Ariani, Kurnia Rina; Sulistyawati, Ardiani Ika; Wijayanti, Rita (Owner : Riset dan Jurnal Akuntansi, 2024)
This study intends to examine how ownership structure affects the amount of disclosure on climate change in the mining sector listed on the Indonesia Stock Exchange from 2018 to 2022. Purposive sampling was used to select a sample of 44 businesses, yielding 216 imbalanced observation data in all. The websites of each company's annual reports are used to gather secondary data. Items for disclosing climate change were taken from Darus, Mohd Zuki, and Yusoff's (2020) declaration of carbon emissions. To find out how much information corporations were disclosing about climate change, content analysis techniques were used. According to the study's findings, just 16.33% of climate change information is now disclosed. To test the theory, panel data regression using a random effect model technique was used. The results highlight the important part that institutional investors have played in pressuring businesses to disclose climate change. Foreign ownership, meanwhile, was determined to have no effect. The findings of this study have indirect repercussions for managers who must consider the low level of investor-required disclosure of climate change as a substantial factor in investment choices. Additionally, legislative rules might be included recognising the crucial contribution that institutional investors contribute to promoting corporate disclosure performance. Keywords: Carbon Emission; Climate Change Disclosure; Content Analysis; Mining Industry; Ownership Structure